Conducting International Diploma Course on Malaria Program Planning and Management (1996–2012) - Mesdaghinia, Ali Reza (Tehran University of Medical Sciences, 2013)
BACKGROUND: Malaria is still a public health problem in the world. One of the main objectives of World Health organization is capacity building of authorities who are involved with malaria control activities. METHODS: The first course was conducted in 1996 in Bandar Abbas Training center. The course was conducted jointly by the Ministry of Health and Medical Education of Iran, WHO-EMRO and School of Public health, Tehran university of Medical Sciences. In year 2002, Iran has been designated as WHO regional Malaria Training Center. Prior to initiate the course, pre-test evaluations including 11 subjects were carried out. The examinations include multiple choice questions. Different methods of teaching including lecture, laboratory, workshop, team work, field exercise and presentation were used. The duration of the course was 9 weeks. A total of 360 contact hours were taught. The main subjects were Basic epidemiology and Simple Statistics, Malaria Parasitology, Malaria disease Management, Malaria Entomology, Vector Control, Epidemiological approach, Filed work and Planning. The requirement for achievement of the course was to have at least 60% of the total mark for awarding the diploma certificate. The 13th course was conducted by the financial support of Islamic Development Bank (IDB). RESULTS: A total of 300 participants from 26 different countries have been graduated from these courses so far. CONCLUSION: This course is providing the skill for decision making, how to combat against malaria in their country and is parallel to the policy of the malaria control for capacity building in malarious areas of the world.